Cost-based optimal distributed generation planning with considering voltage depended loads and power factor of DG - Babak Yousefi-Khangah; Saeed Abapour; Shahram Yousefi-khangah (Majlesi Journal of Electrical Engineering)
If determination of location and size of Distributed Generation (DG) are applied accurately, the DGâs ability will improve the network situation and reduce operation costs. In this paper, various market conditions are considered to maximize the benefit of DGâs presence and make a trade off among advantages of DG, network situation, and Distribution Company (DISCO) owners. To determine the optimal location and size of DG, two methods of the cost minimization and the nodal pricing are combined. In addition to evaluating the impact of parameters such as variation of energy price and load on objective function, effect of these parameters on location and size of DG is considered. To confirm the results, impact of loads which are dependent on voltage and variation of the power factor of the DG units is applied and then Effect of power factor on optimal location and size of DG is shown. A method is proposed for convergence of different results which is caused by different power factors. To observe long-term impact of the DGâs presence in the network, a load growth for five years is considered annually. Study is carried out on IEEE-30 bus test circuit.